Demystifying and Coping with English for Science and Technology - Forchap, Justine (International Journal of Scientific Research and Management (IJSRM), 2022)
AbstractAdvancement in technology acts as a catalyst in the modern world as it constantly challenges old ways of doing things. Its impact on the English language has far reaching consequences in all walks of life. The English language is dynamic, adapting to the development in science and technology, which in turn responds to scientific, technological, social and economic needs.  Teachers of English for science and technology have a new function which is keeping abreast with the galloping advancement in science and technology. A crucial problem for students is using the new words flexibly, and in cases where there are other English meanings, be able to come out of the scientific boundary and  discuss scientific and non-scientific issues confidently Forchap (2016). This calls for hard, careful and thorough work so as to make the teaching and learning of EST meaningful.  Science and technology are problem-solving and so is the English language. It is therefore important to demystify the teaching the teaching of EST in order to solve a problem in the world of science and technology.       In Cameroon, there is a dire need to raise awareness. As pointed out in Forchap (2016) the university authorities cling to the traditional methods of teaching English and resent changes. It is in this light that seminars and workshops are recommended to sensitize teachers of English on this issue. The university authorities are in control of the curriculums which makes it easier for English courses to turn to the right direction which aims at accelerating the growth in English courses to meet the needs of specific discipline.